2015
DOI: 10.1155/2016/2527349
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Fat Grafting Reduces Pain in Irradiated Breast: A Review of Our Experience

Abstract: Introduction. Pain syndromes affect women after conservative and radical breast oncological procedures. Radiation therapy influences their development. We report autologous fat grafting therapeutical role in treating chronic pain in irradiated patients. Materials and Methods. From February 2006 to November 2014, we collect a total of 209 patients who meet the definition of “Postmastectomy Pain Syndrome” (PMPS) and had undergone mastectomy with axillary dissection (113 patients) or quadrantectomy (96 patients).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
46
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 22 publications
0
46
0
Order By: Relevance
“…Needling effect is well known and leads to regeneration itself increasing the production of citokyne and local mediators. 13 The combined effect of fat grafting and use of needles is the responsible of the effect of fat grafting in pain syndromes and both aspects are needed for a full response.…”
Section: Re Sultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Needling effect is well known and leads to regeneration itself increasing the production of citokyne and local mediators. 13 The combined effect of fat grafting and use of needles is the responsible of the effect of fat grafting in pain syndromes and both aspects are needed for a full response.…”
Section: Re Sultsmentioning
confidence: 99%
“…9 Our group extensively adopted such a procedure to treat scar tissue-related pathologies, degenerative diseases, and volume deformities. [9][10][11][12][13][14][15][16][17] In 2006, we were the first to treat patients undergoing mastectomy and axillary dissection followed by radiotherapy, 10 demonstrating the ability of the lipostructure to alleviate PMPS symptoms.…”
mentioning
confidence: 99%
“…Considering the authors' interest for our study, we would like to add our more recent reports where we retrospectively evaluate our 10 years experience on the use of autologous fat grafting in the treatment of PMPS focusing on irradiated breast. 4 We recently confirmed the pain reduction effect of this technique reviewing a total of 120 treated patients, affected by PMPS following mastectomy or quadrantectomy and radiotherapy. In this larger group, we detected a statistically significant reduction in the visual analog scale scores when comparing the assessment performed before and after the treatment.…”
mentioning
confidence: 62%
“…In patients with postmastectomy pain syndrome, several studies revealed that AFT significantly decreased the VAS score versus nonoperated controls, with a mean decrease of >3 points. 11 , 12 , 18 …”
Section: Discussionmentioning
confidence: 99%